2011
DOI: 10.2152/jmi.58.63
|View full text |Cite
|
Sign up to set email alerts
|

Does the bromocriptine-rebound method improve embryo quality?

Abstract: BR method could provide the better embryos and improve the transplantation rate in women with previous unsuccessful ART attempts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Thus, the authors concluded that IVF failure is the consequence of a granulosa cell resistance to prolactin action and that the bromocriptine-induced hypoprolactinemia contributes to the restoration of prolactin responsiveness and, subsequently, improved oocytes maturation [ 87 ]. A more recent study confirmed the results with the BR method [ 88 ]. Bromocriptine was administered daily from day 5 of the preceding cycle until 7 days before ovarian stimulation in women with normal prolactin levels and previous repeated unsuccessful ART in a new long agonist protocol cycle and the results were compared with those of women treated with long agonist protocol only [ 88 ].…”
Section: The Role Of Dopamine Agonist Administration In Ivf Treatmentsupporting
confidence: 66%
See 2 more Smart Citations
“…Thus, the authors concluded that IVF failure is the consequence of a granulosa cell resistance to prolactin action and that the bromocriptine-induced hypoprolactinemia contributes to the restoration of prolactin responsiveness and, subsequently, improved oocytes maturation [ 87 ]. A more recent study confirmed the results with the BR method [ 88 ]. Bromocriptine was administered daily from day 5 of the preceding cycle until 7 days before ovarian stimulation in women with normal prolactin levels and previous repeated unsuccessful ART in a new long agonist protocol cycle and the results were compared with those of women treated with long agonist protocol only [ 88 ].…”
Section: The Role Of Dopamine Agonist Administration In Ivf Treatmentsupporting
confidence: 66%
“…A more recent study confirmed the results with the BR method [ 88 ]. Bromocriptine was administered daily from day 5 of the preceding cycle until 7 days before ovarian stimulation in women with normal prolactin levels and previous repeated unsuccessful ART in a new long agonist protocol cycle and the results were compared with those of women treated with long agonist protocol only [ 88 ]. The number of retrieved oocytes was the same in both groups; however, superior results were obtained with the BR method in terms of the number of fertilized oocytes, cleaved embryos, transplanted embryos, the ratio of good embryos, embryo score, and clinical pregnancy rates.…”
Section: The Role Of Dopamine Agonist Administration In Ivf Treatmentsupporting
confidence: 66%
See 1 more Smart Citation
“…This was attributed to better oocyte maturation which was achieved due to the rebound increase of prolactin after the discontinuation of bromocriptine, which restored post receptor responsiveness in granulosa cells. Moride et al [ 25 ] also concluded that the bromcriptine rebound method yielded morphologically better embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Since PRL improved oogenesis and embryonic development, some researchers have tried to improve the IVF outcomes by prescribing bromocriptine to patients with a history of recurrent implantation failure until the initiation day of rFSH. Therefore, PRL rebounded to a higher level, and the CPR did improve compared to that in the controls (10.1 vs. 27.2% P < 0.05) owing to the significantly increased PRL ( 13 ).…”
Section: Discussionmentioning
confidence: 86%